The Environmental, Social and Governance (ESG) in Accounting: A Review - Huang, Jiamin (Journal of Global Economy, Business and Finance, 2024)
Environmental, social and governance (ESG) is an important standard for the green transformation of enterprises in the new era and is also an important tool for guiding green investment. This article delves into the application of environmental, social, and governance (ESG) in modern corporate finance and accounting. First, this article comprehensively discusses the basic concepts and components of ESG, including environmental protection, social responsibility, and governance transparency. This article elaborates on three aspects of ESG standards and financial accounting practices. Finally, suggestions for strengthening ESG integration in financial accounting and potential future research areas are comprehensively elaborated. The research results of this article demonstrate the effectiveness and challenges faced by the application of ESG in corporate finance, providing suggestions for future sustainable development strategies for enterprises.